Peningkatan Hasil Pembelajaran Bahasa Indonesia Melalui Strategi Student Team Achievement Division (Stad) di SMP Negeri 5 Kendari - Nursiah Nursiah (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2016)
ABSTRACTThis study aims to determine the increase in student learning outcomes in learning Indonesian through the implementation of Cooperative Learning Model STAD (Student Teams Achievement Divisions) having stages of activity: (1) the delivery of the learning objectives; (2) provide information about learning materials; (3) organize the students in the group STAD; (4) Question and answer in the study group; (5) guided study groups who are working together; (6) award; and (7) to evaluate individually. This research uses descriptive research method. Subjects were students of class VIII B SMPN 5 Kendari with the number of 40 people. Data were collected using observation and testing instruments, as well as analyzed quantitatively and qualitatively. The results of study showed that the average grade in the pre-stage cycle of 73.28, increasing to 80.03 in the first cycle, and further increased to 87.93 in the second cycle. Classical completeness increased from 40% at the preliminary stage, to 72.5% in the first cycle, and 97.5% in the second cycle. Student activity increased from 17.5% in the pre-stage of the cycle, to 47.5% in the first cycle, and 82.5 in the second cycle. Thus STAD cooperative learning model can improve student learning outcomes. This research is helpful for teachers of subjects in learning innovation in accordance with the demands of the development of education.Keywords: STAD, learning outcomes, learning innovation ABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatan hasil belajar siswa pada pembelajaran Bahasa Indonesia melaluipenerapanModel Pembelajaran Kooperatif Tipe STAD (Student Teams  Achievement Divisions) yang memiliki tahap-tahap kegiatan: (1) penyampaian tujuan pembelajaran; (2) menyajikan informasi tentang materi pembelajaran; (3) mengorganisir siswa dalam kelompok STAD; (4) Tanya jawab dalam kelompok belajar; (5) membimbing kelompok belajar yang sedang bekerja sama; (6) memberikan penghargaan; dan (7) melakukan evaluasi secara individu.         Penelitian ini menggunakan metode penelitian deskriptif. Subyek ini adalah para siswa kelas VIII B SMPN 5 Kendari yang berjumlah 40 orang. Data dikumpulkan mengunakan instrumen observasi dan tes, serta dianalisa secara kuantitatif dan kualitatif. Hasil belajar menunjukan bahwa rata-rata kelas pada tahap pra siklus 73,28, meningkat menjadi 80,03 pada siklus I, dan selanjutnya meningkat menjadi 87,93 pada siklus II. Ketuntasan klasikal meningkat dari 40% pada tahap pendahuluan, menjadi 72,5 % pada siklus I, dan 97,5% pada siklus II. Aktifitas siswa meningkat dari 17,5 % pada tahap pra siklus, menjadi 47,5 % pada siklus I, dan 82,5 pada siklus II. Dengan model pembelajaran kooperatif tipe STAD akan dapat meningkatkan hasil belajar siswa. Penelitian ini sangat bermanfaat bagi guru-guru mata pelajaran dalam melakukan inovasi pembelajaran sesuai dengan tuntutan dan perkembangan dunia pendidikan.Kata Kunci:  STAD, hasil belajar, inovasi pembelajaran